(untitled) (Psychology Travelogs, 2023)
The article updates the issue of awareness of the global nature of divorce problems in the modern world. This article presents an analysis of psychological research on the problem of divorce. The essence of the concept of "pathologizing roles" that may arise during divorce is specified. It was found that the emergence of pathologizing family roles reflects: a superior, contemptuous, selfish attitude of a person towards family members; weakness, dependence of a person on a marriage partner; propensity of a family member to immoral behavior; the presence of a certain physiological and mental dependence of a family member. The most essential characteristics of the family structure, motives for creating dysfunctional families (escape from parents, duty, loneliness, following traditions, search for material goods, revenge) are considered. The classification of family conflicts (by subject, source, behavior of conflicting parties), stages of divorce (accumulated marital dysfunction or disagreements, reflection and decision-making about divorce, restructuring of the family system and its stabilization), models of experiencing loss and grief (denial, anger) were analyzed , negotiation, depression, acceptance). Ways of reconciliation with divorce, as well as behavioral strategies before divorce are highlighted. Here are tips on how to survive a meltdown and recover faster. The results of an empirical study of the main factors of helping to get out of a crisis state among men and women are highlighted. The breakdown of marital relations leads to a decrease in the social status of an individual, which further affects self-perception, especially for women who, according to others, "have not fulfilled their duty", while men are criticized and more prone to positive self-perception.